PENGEMBANGAN BAHAN AJAR BERBASIS MASALAH PADA MATA KULIAH MATEMATIKA EKONOMI PROGRAM STUDI PENDIDIKAN MATEMATIKA - Rina Agustina; Ira Vahlia (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2016)
Teaching materials are needed for students to support the lecture. The purpose of this study was to determine how to develop problem-based teaching materials on the subjects of mathematical economics mathematics education courses. This research was conducted at the University of Muhammadiyah Metro by selecting a student of mathematics education as a research subject.This study is a research development. The method used as follows: (1) research and information gathering, (2) planning, (3) product development, (4) the initial trials, (5) product revision, (6) the field trials, (7) the revised product field trials, (8) the operational testing of products, (9) the revision of the product and (10) the implementation and dissemination. To obtain problem-based teaching materials will be validated teaching materials by 2 experts math education materials and one person linguists. The achievement of this research is problem-based teaching materials that can support economic mathematics lectures. The achievement that will be produced is ≥ 50% students of mathematics education are getting the optimal learning course on the math economy. Based on the results of questionnaires percentage obtained validation criteria of 80% of teaching materials and meet the criteria are valid for.